PELUANG, TANTANGAN, DAN PROSPEK PERBANKAN SYARIAH INDONESIA DALAM MENGHADAPI PERSAINGAN MASYARAKAT EKONOMI ASEAN (MEA) 2015 - PUTRI AWWALLIN, DHIKA (Jurnal Akuntansi AKUNESA, 2015)
ABSTRACT The purpose of this research is to determine the readiness of Indonesia in the ASEAN Economic Community (AEC) 2015.The purpose of the establishment of the ASEAN Economic Community (AEC) is to create an ASEAN economic region that is prosperous and highly competitive.Implications of the implementation of the ASEAN Economic Community (AEC) on the economy of a country is fully integrated into the global economy to prepare for the free market in the field of capital, goods and services, investment and labor. The growth of Islamic banking in Indonesia each year is relatively high. This increase is reflected in the asset and the number of institutional financing.The government must pay more attention to the development of islamic banking in an effort to improve the quality of islamic banking in Indonesia especially in the ASEAN Economic Community (AEC) by analyzing the terms of the opportunities, challenges, and prospects.   Keyword: AEC, islamic banking, opportunities, challenges, prospects